Approach Restorative In Loss Recovery Caused by Criminal Acts of Corruption - Muhammad Syahnan; Zulkarnain; Noor Azizah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The restorative approach to the recovery of losses caused by criminal acts of corruption offers alternatives that focus on restoring relationships and losses compared to retributive approaches that only emphasize punishment. This study uses a normative juridical method with the law approach to analyze the basic principles of restorative approaches, recovery mechanisms, benefits, challenges, and implementation in Indonesia. The restorative approach is based on the principle of restoring losses, active participation of all parties, and reintegration of the perpetrators. The results of the discussion show that the restorative approach has the potential to increase justice and improve social relations, although there are still significant challenges. The application of this approach in Indonesia requires stronger legal and community support. This study concluded that the restorative approach can improve the law enforcement system with a greater focus on recovery and reintegration. Suggestions for further development include legal reform and increasing community participation to optimize the recovery of losses due to criminal acts of corruption, so that further legal reform is carried out to support restorative mechanisms and increase community participation.